Etiological and Histomorphological studies on early chick mortality in broiler chicken in Kashmir, India - Pradeep Kumar Yadav; Showkat Ahmad Shah; Majid Shafi; Shayaib Ahmad Kamil; Masood Saleem Mir; Mudasir Ali Rather; Ajaz Ahmad Ganaie; Zahoor Ahmad Wani (Open Veterinary Journal)
Background: Early chick mortality is one of the most important problems of poultry industry that cause severe economic losses to the farmers. The chick mortality varies in different geographical locations and its etiological factor also varies.